Effects of a novel fulvic acid-enriched water-soluble fertilizer on potato growth, yield, and water-fertilizer use efficiency under different drip irrigation regimes - Xu, Fulin; Liu, Yi; Li, Jiangtao; Zhu, Jinquan; Wu, Nan; Meng, Ajing (Frontiers in Plant Science, 2025)
Northern China is a major potato-producing region, where water scarcity and low fertilizer use efficiency significantly constrain potato production. A field experiment was conducted in Xinjiang, China, in 2023 using the potato cultivar ‘Xisen 6’ to investigate the effects of a novel fulvic acid (FA)-enriched specialized fertilizer on potato growth, photosynthetic characteristics, yield, and water-fertilizer use efficiency under different drip irrigation levels. Three irrigation regimes were applied: conventional irrigation (W1: 4582.5 m3·ha-1), 15% deficit irrigation (W2: 3865.5 m3·ha-1), and 30% deficit irrigation (W3: 3165 m3·ha-1). Five fertilization treatments were implemented: no fertilizer (CK), conventional fertilizer (CF), and three FA-enriched formula fertilizers—F1 (FA: 120 g·L-1, N-P-K = 110-100-120), F2 (FA: 60 g·L-1, N-P-K = 130-120-150), and F3 (FA: 30 g·L-1, N-P-K = 170-150-130). The results indicated that both irrigation (W) and fertilization (F) significantly influenced potato growth, yield, and the efficiency of water and fertilizer use. Under W2 irrigation, the W2F2 treatment achieved optimal performance, with plant height, aboveground dry weight, SPAD, and tuber yield increasing by 56.67%, 71.24%, 21.69%, and 121.29%, respectively, compared to CK. WUE and PFP reached 13.84 kg·m-3 and 100.1 kg·kg-1, respectively, while maintaining a yield of 59.49 t·ha-1 under 15% water-saving conditions. Tuber yield exhibited highly significant positive correlations with plant height, aboveground dry weight, SPAD, net photosynthetic rate, WUE, and PFP. Principal component analysis based on growth, yield, and resource use efficiency identified W2F2 as the highest-ranked treatment. In conclusion, for ‘Xisen 6’ cultivation in Northwest China, applying formula fertilizer F2 (FA: 60 g·L-1, N-P-K = 130-120-150) under a drip irrigation rate of 3865.5 m3·ha-1 significantly enhances plant growth, yield, and water use efficiency, providing a sustainable strategy for optimizing potato production.